DEICTIC ANALYSIS OF MINEFIELDS SONG LYRIC BY FAOUZIA FEAT. JOHN LEGEND - Illiyin, Zainata; Kusworo, Budik (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
This study aims to analyze the types and the references of deictic words which found in the